IMPLEMENTASI PERMAINAN KATANI-TANI PADA ANAK USIA DINI DI KELURAHAN WAKOKO, KECAMATAN PASARWAJO, KABUPATEN BUTON - Hapsari, Sitti; Henny, Henny; Saleh, Rachman (SINERGI : Jurnal Riset Ilmiah, 2025)
Early childhood the age range of 0 to 8 years is an individual figure who is undergoing a rapid and fundamental development process for the next life. The application of traditional games in early childhood learning is intended to explore their needs. The implementation of traditional games is one way to preserve Indonesian culture. Katani-tani games make children more active, disciplined and able to work together with their friends. Katani-tani games have benefits for early childhood and make children more active, disciplined and responsible and understand the concept of cooperation in a game. Traditional games have their own richness compared to modern games that are currently booming. Traditional games are still chosen in some circles of society, especially children who need games that can explore their needs. Through this katani-tani game, children can also be taught to regulate their emotions and social . It can be stated that the katani-tani game is able to optimize children's abilities in increasing agility, helping children to be honest, responsible and